Polyethylenimine quantity and molecular weight influence its adjuvanting properties in liposomal peptide vaccines. (15th May 2021) - Dai, Charles C.; Huang, Wenbin; Yang, Jieru; Hussein, Waleed M.; Wang, Jingwen; Khalil, Zeinab G.; Capon, Robert J.; Toth, Istvan; Stephenson, Rachel J.
Graphical abstract: Abstract: We recently reported that polyethylenimine (PEI; molecular weight of 600 Da) acted as a vaccine adjuvant for liposomal group A Streptococcus (GAS) vaccines, eliciting immune responses in vivo with IgG antibodies giving opsonic activity against five Australian GAS clinical isolates. However, to date, no investigation comparing the structure–activity relationship between the molecular weight of PEI and its adjuvanting activity in vaccine development has been performed. We hypothesized that the molecular weight and quantity of PEI in a liposomal vaccine will impact its adjuvanting properties. In this study, we successfully formulated liposomes containing different molecular weights of PEI (600, 1800, 10k and 25k Da) and equivalents of PEI (0.5, 1 and 2) of branched PEI. Outbred mice were administrated the vaccine formulations intranasally, and the mice that received a high ratio of PEI 600 reported a stronger immune response than the mice that received a lower ratio of PEI 600. Interestingly, mice that received the same quantity of PEI 600, PEI 10k and PEI 25k showed similar immune responses in vivo and in vitro . This comparative study highlights the ratio of PEI present in the liposome vaccines impacts adjuvanting activity, however, PEI molecular weight did not significantly enhance its adjuvanting properties. We also report that the stability of PEI liposomes is critical for vaccines to elicit the desired immune response.